Treatment of refractory Wegener's granulomatosis with humanized monoclonal antibodies. - Lockwood, C; Thiru, S; Stewart, S; Hale, G; Isaacs, J; Wraight, P; Elliott, J; Waldmann, H (1996)
Conventional immunosuppression for systemic vasculitides is limited by substantial side-effects, cumulative drug toxicity and refractoriness in some patients. Six Wegener's granulomatosis patients who had been refractory to conventional therapy for at least 6 months, were treated with humanized monoclonal antibodies specific to lymphocyte CD52 or CD4 antigens. Diagnosis was on clinicopathological grounds, supported by the presence of autoantibodies to Proteinase 3. Histological evidence of persistent disease activity was obtained for each patient. Humanized monoclonal anti-CD52, with or without anti-CD4, was given intravenously up to 40 mg/day for up to 10 days. Remission, (programmed withdrawal of drug therapy without return of refractory disease) was achieved in all patients. Cytotoxic drugs were discontinued at the time of monoclonal antibody treatment and not used again; steroids were withdrawn gradually. Four patients relapsed at 1.5, 5, 10 and 18 months, and were treated successfully with further monoclonal antibody therapy alone. Three years after the study began, five patients are well; one patient died at surgery whilst in remission. Humanized monoclonal antilymphocyte antibodies may provide an effective treatment in patients with systemic vasculitis which is refractory to steroids or cytotoxic agents, or who are intolerant of these drugs.